LANGUAGE ERRORS IN BIOGRAPHICAL TEXT ESSAYS BY STUDENTS OF CLASS X SMA AL HIKMAH SURABAYA - Trias Puguh Jatmiko, Henry; Bagus Permadi, Sugeng; Muhammad Rifai, Dian (Melekliterasi Press, 2024)
This study aims to describe gender-based student language errors in the areas of spelling, sentences, and word choice in biographical texts written by class X students of SMA Al Hikmah Surabaya. The research used qualitative method with descriptive qualitative approach. The research subjects were X1 and X2 male, X6 and X7 female, and two Indonesian language teachers. The research was conducted at SMA Al Hikmah Surabaya. Data collection techniques in this study were documentation and semi-structured interviews. The research data analysis technique used Miles and Huberman's interactive analysis model, including data collection, data condensation, data presentation, and withdrawal. the validity of the research data used credibility, confirmability, and dependability tests. The results of this study show that language errors contained in biographical texts written by male students include 154 errors in spelling with a percentage of 81%, 30 errors in sentences with a percentage of 15.78%, and 6 errors in word choice with a percentage of 3%. There are three factors that cause language errors in male students, namely, 1) mastery of Indonesian language rules that have not been maximized, 2) lack of knowledge about Indonesian grammar book references, and 3) Indonesian language teaching that has not been maximized.